2004
DOI: 10.1080/00480169.2004.36455
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clonal diversity of Campylobacter jejuni from dairy farms and urban sources

Abstract: Cattle, sparrows, rodents and flies are potential reservoirs of C. jejuni on dairy farms. Identical clones of C. jejuni carried by cattle, sparrows, flies and rodents probably indicate a common source of infection. The high level of asymptomatic carriage of C. jejuni by healthy dairy cows could be sufficient to maintain infections within the dairy farm surroundings via environmental contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
11
25
0
Order By: Relevance
“…Possible vehicles for strain dissemination may include insects, other animals, groundwater, or human traffic (6,15,30,31). Clonal groups were also identified among multidrug-resistant C. coli isolates from turkeys in this region (9,22), as well as among C. coli and C. jejuni isolates from cattle and other meat animals (2,5,11,20).…”
Section: Discussionmentioning
confidence: 92%
“…Possible vehicles for strain dissemination may include insects, other animals, groundwater, or human traffic (6,15,30,31). Clonal groups were also identified among multidrug-resistant C. coli isolates from turkeys in this region (9,22), as well as among C. coli and C. jejuni isolates from cattle and other meat animals (2,5,11,20).…”
Section: Discussionmentioning
confidence: 92%
“…We found that while the pads were in use Campylobacter were also recovered from drainage but in lower numbers than E. coli. in contrast to E. coli that is shed by all the animals in a herd, Campylobacter will be shed by only those cows that are infected at any one time; reported to be about 50% by Adhikari et al (2004) and found to range from about 40-70% (AgResearch unpubl. results).…”
Section: Faecal Bacteria In Stand-off Pads and Drainagementioning
confidence: 99%
“…Most cases of campylobacteriosis are sporadic, and, unusually for an enteric pathogen, there is apparently limited person-to-person transfer. Transfer among animal species appears to occur readily as recovery of Campylobacter jejuni with a very similar genetic composition (indicated by the pulsed-field gel electrophoresis pattern) was reported from the faeces of cows, sparrows, rodents and from flies on a dairy farm in the Manawatu (Adhikari et al 2004). Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%